Gender Discrimination as a Legal Crisis Challenges to Protection in the Indonesian Criminal System - Hasrah, Nur; Arsyad, Nasrullah; Iqbal, Muhammad Nur (Faculty of Law, Universitas Muslim Indonesia, 2025)
This study aims to determine and analyze legal protection for victims of gender discrimination in Indonesian criminal law, especially based on Law Number 39 of 1999 concerning Human Rights. The research method used is normative legal research with a statutory and conceptual approach. The results of the study indicate that Law Number 39 of 1999 has regulated the principles of gender equality and protection against discrimination, but its implementation still faces various challenges. There are still gaps in the application of the law, weak enforcement of sanctions against perpetrators of gender discrimination, and minimal public awareness of their rights. In addition, this study also discusses the relationship with the Convention on the Elimination of All Forms of Discrimination Against Women (CEDAW), which has been ratified by Indonesia but has not been fully implemented in the national legal system. strengthening regulations for the government and legislative institutions to formulate legal policies that are more responsive to gender discrimination issues. In addition, law enforcement officers and human rights protection institutions such as the National Commission on Violence Against Women and the National Human Rights Commission are also recommended to increase the effectiveness of case handling and victim advocacy. Increasing public legal awareness through gender-based legal education is also important so that legal protection can run optimally.